Investigating the Effects of Media Consumption on Attitudes Toward Police Legitimacy. Issue 8 (3rd August 2018) - Intravia, Jonathan; Wolff, Kevin T.; Piquero, Alex R.
ABSTRACT: Prior investigations have examined both traditional media (e.g., television news) and entertainment media (e.g., crime-related shows) on policing-related outcomes; however, less is known how contemporary forms of media, such as the Internet and social media, may affect policing-related outcomes. Using a sample of young adults, the current study examines the effect of multiple types of media consumption (traditional, entertainment, the Internet, and social media) on attitudes toward police legitimacy. Findings reveal that respondents who read news online are more likely to have negative attitudes toward police legitimacy. However, when individual differences are controlled for, the effect of reading news online is weakened and using social media becomes marginally significant. Further, the impact of media consumption on attitudes toward police legitimacy varies by key audience characteristics.